Exploring the radiographic distinctions between ewing's sarcoma and malignant and fibrous ameloblastoma: a clinical case report and review - Jamil, Nur Aini; Epsilawati, Lusi; Lita, Yurika Ambar (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: Ewing's sarcoma and fibrous ameloblastoma are distinct entities that can present similarly in imaging studies, posing challenges in accurate diagnosis. This report aims to elucidate the radiographic features that differentiate these two lesions. Case Report: The first case was a 7-year-old boy who came to the radiology installation accompanied by his mother for a panoramic radiography examination. The patient complained of swelling on both sides of the lower jaw for 1.8 years. The second case was an 8-year-old boy who came with a referral for a panoramic radiography examination due to swelling on the left side of the lower jaw for 6 months. The first case was radiographically determined as Differential Radiodiagnosis Ewing sarcoma and malignant ameloblastoma, and the second case was radiographically determined as fibrous ameloblastoma with differential Radiodiagnosis malignant ameloblastoma. The differential diagnosis between Ewing's sarcoma and fibrous ameloblastoma is critical due to their distinct treatment protocols and prognoses. This case underscores the importance of comprehensive imaging evaluation and correlating clinical findings to achieve an accurate diagnosis. Conclusion: This case report contributes to the understanding of radiographic distinctions among Ewing's sarcoma, fibrous ameloblastoma, and malignant ameloblastoma. Enhanced awareness of these differences may improve diagnostic accuracy and inform treatment strategies. This abstract provides a succinct overview of the case report, highlighting essential elements such as background information, case details, discussion points, and conclusions relevant to radiographic distinctions between the two conditions.